Special Considerations in the Care of Women With Advanced Heart Failure - Ebong, Imo A.; DeFilippis, Ersilia M.; Hamad, Eman A.; Hsich, Eileen M.; Randhawa, Varinder K.; Billia, Filio; Kassi, Mahwash; Bhardwaj, Anju; Byku, Mirnela; Munagala, Mrudala R.; Rao, Roopa A.; Hackmann, Amy E.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Advanced heart failure (AHF) is associated with increased morbidity and mortality, and greater healthcare utilization. Recognition requires a thorough clinical assessment and appropriate risk stratification. There are persisting inequities in the allocation of AHF therapies. Women are less likely to be referred for evaluation of candidacy for heart transplantation or left ventricular assist device despite facing a higher risk of AHF-related mortality. Sex-specific risk factors influence progression to advanced disease and should be considered when evaluating women for advanced therapies. The purpose of this review is to discuss the role of sex hormones on the pathophysiology of AHF, describe the clinical presentation, diagnostic evaluation and definitive therapies of AHF in women with special attention to pregnancy, lactation, contraception and menopause. Future studies are needed to address areas of equipoise in the care of women with AHF.